Simulação de ensaios de puncionamento esférico utilizando o método dos elementos finitos - Almeida, Luiz Fernando Maia de (2017)
The Small Punch Test, a technique that is not very used in Brazil yet, presents as an alternative to conventional tests for the evaluation of mechanical properties and can be considered non-destructive, since it requires small specimen to be tested. The objective of this study is to perform numerical simulations of these tests to analyze this technique, as well as verify the sensitivity of the results to the variation of some parameters. Numerical experiments, when well validated, allow the analysis of several test parameters in an easier, faster and less expensive way than physical experiments. The simulations were performed using STAMPACK®, a finite element software which uses explicit-dynamic integration in its algorithm. The numerical model was validated with Small Punch Tests carried out on instrumented equipment, in which different steels were tested. This comparison allowed equipment compliance to be estimated, making it possible to correct this effect in the experimental results. Among the test parameters evaluated in this study, the clamping force showed little influence on the results, except for extreme cases. Specimen thickness had influenced on the behavior of the test curve, so that thicker specimens led to lower transition between the test stages as well as higher loads, when compared to thinner specimens. As for the friction, it was observed that only the last part of the test, close to the maximum load, was affected. Its effect also changed the specimen behavior in the rupture. Finally, expressions were obtained to estimate yield strength and ultimate tensile strength. They showed good results, mainly for the yield strength, for which the errors were less than 5%.